1984
DOI: 10.1002/ijch.198400003
|View full text |Cite
|
Sign up to set email alerts
|

Reactions of Alkoxy Radicals in Aqueous Solutions

Abstract: The kinetic and mechanistic properties of alkoxy radicals in organic solvents are briefly reviewed. Owing to the scarcity of such data in aqueous solutions and since reactions at the membrane/water interface may be also biologically important, we have studied the reactivity of these radicals in water and the results of our investigations are reported. Alkoxy radicals were generated by photolytic or radiolytic cleavage of peroxide precursors (tert‐butyl hydroperoxide and di‐tert‐butyl peroxide as well as hydrop… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
17
0

Year Published

1984
1984
2020
2020

Publication Types

Select...
6
3

Relationship

0
9

Authors

Journals

citations
Cited by 39 publications
(19 citation statements)
references
References 114 publications
2
17
0
Order By: Relevance
“…H + /-BuOOH CH2C(CH3)2OOH + H2 (17) OH + /-BuOOH -» t-BuOO + H 20 (18) OH + /-BuOOH -* CH2C(CH3)2OOH + H20 (19) The form ation of the /-butoxyl radical /-BuO can be m onitored by product analysis since it de composes very rapidly (/1/2 ~ 1 //s [21,22]) into acetone, the key product for this study, and a methyl radical (reaction (21)). These radicals are also produced in a bimolecular decay (reaction (20)) o f the /-butylperoxyl radicals.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…H + /-BuOOH CH2C(CH3)2OOH + H2 (17) OH + /-BuOOH -» t-BuOO + H 20 (18) OH + /-BuOOH -* CH2C(CH3)2OOH + H20 (19) The form ation of the /-butoxyl radical /-BuO can be m onitored by product analysis since it de composes very rapidly (/1/2 ~ 1 //s [21,22]) into acetone, the key product for this study, and a methyl radical (reaction (21)). These radicals are also produced in a bimolecular decay (reaction (20)) o f the /-butylperoxyl radicals.…”
Section: Resultsmentioning
confidence: 99%
“…The term ination rate constants of C H 2C (C H 3)2OOH and t-BuOO were assumed to represent diffusion control (reac- tions (32) and (33)) except for the self-termination of /-BuOO' which was taken at 2.5 * 104 dm 3 m ol-1 s"1 [33]. The situation to be modeled is com plicat ed; upon term ination o f peroxyl radicals with each other, some oxygen is formed that reacts with C H 2C (C H 3)2OOH; methyl radicals from reac tion (21) are also present.…”
Section: Chain Reaction Upon O H Radical Attackmentioning
confidence: 99%
“…130 The chemical reactivity of ROO and RO is determined by their a-substituents. 130,142,143 The reaction of O 2 À with NO yields the strong oxidant peroxynitrite, ONOO À (Scheme 1, reaction 8), which can react with wide array of biological entities, including DNA and proteins. 144,145 Protonation of ONOO À forms peroxynitrous acid, which can undergo homolytic cleavage to form OH and nitrogen dioxide (Scheme 1, reaction 9b).…”
Section: Nature and Properties Of Rosmentioning
confidence: 99%
“…The spin trapping of secondary alkoxyl radicals in aqueous systems has proven difficult, apparently because of their rapid cyclization. However, product analysis and spin-trapping investigations have demonstrated that fatty acid alkoxyl radicals undergo intramolecular epoxidation [10,14,15,18], β-scission [15,18,19] and intermolecular reactions [20].…”
Section: Introductionmentioning
confidence: 99%